2011
DOI: 10.1371/journal.pone.0015228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Residues of the Mycobacterial Dephosphocoenzyme A Kinase by Site-Directed Mutagenesis

Abstract: Dephosphocoenzyme A kinase performs the transfer of the γ-phosphate of ATP to dephosphocoenzyme A, catalyzing the last step of coenzyme A biosynthesis. This enzyme belongs to the P-loop-containing NTP hydrolase superfamily, all members of which posses a three domain topology consisting of a CoA domain that binds the acceptor substrate, the nucleotide binding domain and the lid domain. Differences in the enzymatic organization and regulation between the human and mycobacterial counterparts, have pointed out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Our other mutational studies have shown that conserved residues of the Walker A/P-loop motif are critical for LpxK function, as has been observed for other P-loop kinases (39,40). Mutation of three P-loop glycine residues inhibited activity significantly, especially those nearer the conserved P-loop lysine.…”
Section: Lpxk Mutantsupporting
confidence: 68%
See 1 more Smart Citation
“…Our other mutational studies have shown that conserved residues of the Walker A/P-loop motif are critical for LpxK function, as has been observed for other P-loop kinases (39,40). Mutation of three P-loop glycine residues inhibited activity significantly, especially those nearer the conserved P-loop lysine.…”
Section: Lpxk Mutantsupporting
confidence: 68%
“…First, only LpxK incubated with ATP/Mg 2+ crystallized with ADP and Mg 2+ in the active site, indicating that ATPase activity may have been achieved in the absence of DSMP during crystallization. Second, in other P-loop kinases, the Walker A hydroxyl-containing residue (T52 in LpxK), which follows the P-loop lysine, is often found to be directly involved in Mg 2+ binding (19)(20)(21)(22) and is sometimes assisted by a Walker B carboxylate (19,20,31,40). The precatalytic conformation of ATP/Mg 2+ -bound LpxK may be well-represented by the GTPγS/Mg 2+ -bound model of LpxK's closest structural homolog HypB, in which the γ-phosphate occupies an analogous position to the Mg 2+ ion of the LpxK structure (Fig.…”
Section: Lpxk Mutantmentioning
confidence: 99%
“…All previously characterized DPCKs are considered to be ATP dependent, although direct experimental evidence is limited. In bacteria, DPCK enzymes from Thermus thermophilus HB8 (31), Mycobacterium tuberculosis (3234), Streptomyces peucetius ATCC 27952 (35), and E. coli K-12 (36) have been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the primers, C235S_Fwd: 5′ –GATCGCGTCCGGGCATAAGGCCTTG- 3′ and C235S_Rev: 5′ –ATGCCCGGACGCGATCTTTAG- 3′ and the set, C368S_Fwd: 5′ –GAAGACTATTTGACGGTCAAGTCTGACGCCGACAG- 3′ and C368S_Rev: 5′-GTCGGCGCGCCTGTCGGCGTCAGACTTGACC- 3′ , the CoaE cysteine mutants, C235S and C368S, were PCR-amplified from the mycobacterial genomic DNA using the same conditions as the wild type protein described in [17] . The cysteine mutant proteins were expressed and purified like wild type CoaE [17] , [19] .…”
Section: Methodsmentioning
confidence: 99%